The occurrence of some foodborne pathogens recovered from poultry meat in Shahrekord, Iran (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Arcobacter butzleri, Listeria monocytogenes, Staphylococcus aureus, and Campylobacter jejuni are significant foodborne pathogens regarding the consumption of raw poultry meat. An existing survey was conducted to assess the occurrence of S. aureus, C. jejuni, A. butzleri, and L. monocytogenes in raw poultry meat samples. Materials and Methods: Ninety-four raw ostrich, turkey, chicken, and quail meat samples were collected and subjected to culture-based analysis. Staphylococcus aureus, C. jejuni, A. butzleri, and L. monocytogenes isolates were confirmed by standard biochemical techniques. Results: The occurrence of A. butzleri, C. jejuni, L. monocytogenes, and S. aureus in poultry meat samples was 11.45%, 17.70%, 1.04%, and 16.66%, respectively. L. monocytogenes was absent in chicken, turkey, and ostrich meat samples. Only one quail meat (4.16%) was positive for L. monocytogenes. The uppermost contamination rate with A. butzleri, C. jejuni, and S. aureus was found in chicken (25%), turkey (25%), and turkey (25%) meat samples, respectively. The concurrent occurrence of A. butzleri + C. jejuni + S. aureus bacteria amid the examined poultry meat samples was 2.08%. Conclusion: This is an initial report of A. butzleri, S. aureus, C. jejuni, and L. monocytogenes in poultry meat samples. Adequate cooking of poultry meat can diminish foodborne diseases due to A. butzleri, S. aureus, L. monocytogenes, and C. jejuni bacteria, and these species may constitute a public health problem. J. Adv. Vet. Anim. Res., 10(2): 205–210, June 2023http://doi.org/10.5455/javar.2023.j670